Contribution of public places in proliferation of dengue vectors in Penang Island, Malaysia - Maimusa, Alhaji Hamisu; Ahmad, Abu Hassan; Abu Kassim, Nur Faeza; Ahmad, Hamdan; Dieng, Hamady; Rahim, Junaid (Elsevier, 2017)
Objective: To determine abundance, distribution and diversity of potential breeding container habitats of the dengue vectors in public places including schools, restaurants, mosques and parks in southwest areas of Penang Island, Malaysia. Methods: Premises at restaurants, schools, parks and mosques were surveyed simultaneously and inspected visually for container habitats and production of immature mosquitoes from March 2015 to March 2016. Abundance (mean ± SE) of breeding containers between sites was compared using One-way ANOVA. Independent sample ttest was used to compare total number of Aedes albopictus (Ae. albopictus) and Aedes aegypti (Ae. aegypti) surveyed. Results: The surveyed locations yielded a total of 3741 breeding containers and 19537 immature mosquitoes from four areas. Concurrent artificial and natural containers produced 78.4% immature Ae. albopictus and 6.3% Ae. aegypti mosquitoes in wet season, with 14.2% Ae. albopictus and 1.1% Ae. aegypti mosquitoes in dry season. Artificial containers accounted for 98.1% of the total containers recorded, with restaurants being the most productive locations (8 012) and schools being the least productive (2 234). Conclusions: It was concluded that public places are good sources of potential container habitats of Aedes mosquitoes in Penang Island, Malaysia and Ae. albopictus has exclusively replaced the home-grown Ae. aegypti even in urban areas. Therefore, treatment of artificial containers in such locations is critical in Aedes mosquito control campaigns during dengue outbreaks.